Análise de desempenho de redes sem fio de baixo consumo energético por meio de simuladores de eventos discretos - Barros, Joao Luis Verdegay de (2023)
The Internet of Things (IoT) has been a highly relevant topic in both academia and industry in recent years. There are many possible applications, in fields as smart cities, home automation, smart buildings, agriculture, automated metering, logistic, industrial automation. Such a wide range of applications has led to the development of various technological solutions, particularly to enable Machine-to-Machine (M2M) communications, which we highlight those for wide area networks. In that sense, two widely used protocols for Low-Power Wide-Area Networks(LPWAN) communications are: Long Range Wide Area Network (LoRaWAN), and 6TiSCH. LoRaWAN uses the physical layer defined by LoRa, whereas 6TiSCH is based on IEEE 802.15.4e which introduces TSCH (Time-Slotted Channel Hopping) mode as a new operating mode of the MAC layer alongside IEEE 802.15.4g which also has MAC and physical (PHY) layer definitions. While LoRaWAN is a well-known and widespread protocol, 6TiSCH offers IPv6 connectivity for LPWAN and it is used in important standards such as Wireless Smart Ubiquitous Network (Wi-SUN). The objective of this study is to assess the scalability of each protocol, considering various aspects such as packet loss rate (PER), delay, and the maximum number of nodes per square area. Additionally, for 6TiSCH, we evaluate packet losses caused by common transmission failures, such as full queues and the limit of additional transmission attempts. To achieve these results, computer simulations were conducted using open-source simulators. The obtained results demonstrate that the best scalability depends on which scenarios are considered. In scenarios with multiple gateways requiring low latency or low packet transmission rates, LoRaWAN shows better results. However, in scenarios with high packet transmission rates and where latency is not a significant concern, 6TiSCH is more suitable. Furthermore, even in the best case, the latency associated with LoRaWAN technology can be considerably lower than that associated with 6TiSCH. Moreover, specifically regarding 6TiSCH, we observe that the increase in the maximum number of transmission attempts has a significantly greater impact on the system scalability compared to an increase in the transmission queue size, leading to higher memory consumption in the devices.